Impaired Arterial Elastic Properties and Endothelial Glycocalyx in Patients with Embolic Stroke of Undetermined Source - Ikonomidis, Ignatios; Frogoudaki, Alexandra; Vrettou, Agathi-Rosa; Andreou, Ioannis; Palaiodimou, Lina; Katogiannis, Konstantinos; Liantinioti, Chryssa; Vlastos, Dimitrios; Zervas, Paschalis; Varoudi, Maria; Lambadiari, Vaia; Triantafyllidi, Helen; Pavlidis, George; Efentakis, Panagiotis; Tsoumani, Maria; Tsantes, Argirios E.; Parissis, John; Revela, Ioanna; Andreadou, Ioanna; Tsivgoulis, Georgios (Thrombosis and Haemostasis, 2019)
Background and Purpose Cardioembolism is a postulated mechanism of embolic stroke of undetermined source (ESUS). We investigated endothelial glycocalyx, aortic elastic properties, oxidative stress, and their association with left atrial (LA) function in ESUS and healthy individuals.Methods In 90 ESUS patients (age 50.4 ± 13.2) and 90 controls with similar risk factors, we measured: (1) perfused boundary region (PBR) of the sublingual arterial microvessels (range 5–25 µm), a marker inversely related with glycocalyx thickness, (2) pulse wave velocity (PWV), central systolic blood pressure (cSBP), and augmentation index (AIx), (3) LA volume and strain using speckle-tracking imaging, and (4) malondialdehyde (MDA) and protein carbonyls (PCs), as oxidative stress markers.Results Compared with controls, ESUS had higher PWV, PBR, MDA, and PC levels as well as higher LA volume and reduced reservoir LA strain (p < 0.05). PBR > 1.2 μm of microvessel ranging from 5 to 9 μm and PWV > 10.2 m/s were associated with ESUS on multivariable analysis (odds ratio: 2.374 and 5.429, p < 0.05, respectively) and increased the c-statistic of the initial model from 0.54 to 0.71. In ESUS, glycocalyx damage (increased PBR) was related with increased PWV (p < 0.01) which was linked with LA reservoir strain after controlling for age, sex, and risk factors (p = 0.03). Increased MDA and PC were related with glycocalyx damage, increased PWV (r = 0.67 and r = 0.52), AIx, cSBP, and aortic atheroma (p < 0.01).Conclusion Arterial function and endothelial glycocalyx are severely impaired in ESUS and are linked to LA dysfunction suggesting their contribution to ESUS pathogenesis.Clinical Trial Registration URL-http://www.clinicaltrials.gov. Unique identifier: NCT03609437.
Keywords: embolic stroke of undetermined source; endothelium; glycocalyx; left atrium; cardiac; pulse wave velocity